2019
DOI: 10.3389/fevo.2019.00334
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Phonotaxis Performance Index to Uncover Signal Selectivity in Walking Phonotaxis

Abstract: Any sensory strategies that prey take to avoid eavesdropping predators will depend on the behavioral decisions of eavesdroppers. As these decisions are guided by the sensory processing of communication signals, accurate measurements of sensorimotor output will provide insights into signal preferences, parameters evaluated for signal recognition, and the perceptual and cognitive capacity of receivers. A number of techniques have been proposed for measuring walking phonotaxis (and taxis behavior more generally).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 84 publications
8
16
0
Order By: Relevance
“…This optical mouse sensor registers motion as changes in x and y pixel units at a sampling rate of 2160 Hz [56]. In a previous study [49], we confirmed that O. ochracea never caused the spherical treadmill to rotate on its axis and thus a single sensor system is sufficient for recording O. ochracea walking phonotactic responses. Data captured from the treadmill system was synchronized with sound presentation using software (StimProg V6) developed in MATLAB (R2018a, The MathWorks Inc., USA) that interfaced with National Instruments Data Acquisition hardware (NI USB-6363, USA).…”
Section: Methodssupporting
confidence: 77%
See 3 more Smart Citations
“…This optical mouse sensor registers motion as changes in x and y pixel units at a sampling rate of 2160 Hz [56]. In a previous study [49], we confirmed that O. ochracea never caused the spherical treadmill to rotate on its axis and thus a single sensor system is sufficient for recording O. ochracea walking phonotactic responses. Data captured from the treadmill system was synchronized with sound presentation using software (StimProg V6) developed in MATLAB (R2018a, The MathWorks Inc., USA) that interfaced with National Instruments Data Acquisition hardware (NI USB-6363, USA).…”
Section: Methodssupporting
confidence: 77%
“…Walking phonotactic responses were recorded from flies tethered and held on top of a spherical treadmill system previously described in [56] and [49]. This treadmill system consists of a spherical ping-pong ball held afloat in a custom holder with a continuous air stream.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, it is possible that host recognition is broadly tuned, accepting differences of call characteristics of multiple host species (sensu Lee et al, 2019;Sakaguchi & Gray, 2011). Based on the hosts from our study, O. lineifrons was attracted to calls that were either interrupted ("versed") or continuous and consisted of single or double pulses.…”
Section: Natural Selection and Possible Adaptations Of Host Speciesmentioning
confidence: 88%